PERAN EDUKASI LITERASI KEUANGAN DAN PERILAKU KEUANGAN DALAM MENINGKATKAN PERTUMBUHAN USAHA BERKELANJUTAN (UMKM YOGYAKARTA ) - Sofiati; Linawati (Jurnal Ekonomi Bisnis Manajemen Prima, 2026)
The growth of sustainable MSMEs is still hampered by low levels of financial literacy and financial behavior of business actors in managing their finances. This study aims to analyze the role of financial literacy education and financial behavior in increasing the growth of sustainable MSMEs in Yogyakarta. This study uses a descriptive qualitative approach with interview, observation, and documentation techniques on business actors who have participated in financial literacy and financial behavior education programs in community service activities. The results of the study indicate that financial literacy education plays a role in increasing sustainable business growth. With a variety of educational themes, participants are able to implement them in managing finances, thus impacting the increase in sustainable business growth. The findings of this study are the results of education in the community service program that with different financial literacy education themes and different business characteristics, business actors are able to achieve sustainable business growth. In addition, to improve business actors in financial behavior, it is necessary to find a training model and mentoring in financial management. The results of this study contribute to business actors to always improve their understanding of financial literacy and financial behavior so that business sustainability develops. The results of this study also serve as input for further research. The results of community service activities should be continued as research material so that there is real synergy in developing MSME business growth.